Unraveling spatially heterogeneous ultrafast carrier dynamics of single-layer WSe2 by femtosecond time-resolved photoemission electron microscopy - Wang, Lin (2020)
Studies of the ultrafast carrier dynamics of transition metal dichalcogenides have employed spatially averaged measurements, which obfuscate the rich variety of dynamics that originate from the structural heterogeneity of these materials. Here, we employ femtosecond time-resolved photoemission electron microscopy (TR-PEEM) with sub-80 nm spatial resolution to image the ultrafast subpicosecond to picosecond carrier dynamics of monolayer tungsten diselenide (WSe2). The dynamics observed following 2.41 eV pump and 3.61 eV probe occurs on two distinct time scales. The 0.1 ps process is assigned to electron cooling via intervalley scattering, whereas the picosecond dynamics is attributed to exciton-exciton annihilation. The 70 fs decay dynamics observed at negative time delay reflects electronic relaxation from the Γ point. Analysis of the TR-PEEM data furnishes the spatial distributions of the various time constants within a single WSe2 flake. The spatial heterogeneity of the lifetime maps is consistent with increased disorder along the edges of the flake and the presence of nanoscale charge puddles in the interior. Our results indicate the need to go beyond spatially averaged time-resolved measurements to understand the influence of structural heterogeneities on the elementary carrier dynamics of two-dimensional materials.